TEKNIK PEWARNAAN ALAM ECO PRINT DAUN UBI DENGAN PENGGUNAAN FIKSATOR KAPUR, TAWAS DAN TUNJUNG - D. S., Bayu Wirawan; Alvin, M. Alvin (JURNAL LITBANG KOTA PEKALONGAN, 2019)
Natural dyes is a coloring technique using raw materials from nature, the absorbed color will blend with the fibers in the fabric. Every plant has the potential to be fabric dyes. The ecoprint and ecodyeing technique is defined as the process of transferring colors and shapes to fabric through direct contact. The purpose of this study was to compare the results of the natural coloring technique of sweet potato leaf ecoprint with the use of chalk, alum and tunjung fixators. The natural coloration of ecoprint sweet potato leaves with chalk, alum and tunjung fixators, has several different results. From the results of the study concluded that the manufacture of ecoprint fabric with sweet potato leaves must use a fixing agent as a color locking agent and chalk fixator is superior to be used in the fixation process because if the fabric is washed it does not fade easily . Keywords: Natural dyes, Ecoprint, Fixator